2003
DOI: 10.1021/jf026156v
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acids Alter the Fatty Acid Composition and Physical Properties of Egg Yolk and Albumen

Abstract: Effects of dietary conjugated linoleic acids (CLAs) and docosahexaenoic acid (DHA) on the fatty acid composition of different egg compartments after storage were studied. Four dietary treatments [supplemented with safflower oil (SAFF, control group), DHA, CLAs plus DHA (CAD), and CLAs alone] were administered to Single Comb White Leghorn (SCWL) laying hens. Eggs from the different treatment groups were collected and stored for 10 weeks at 4 degrees C before analysis. Fatty acids from the yolk (yolk granules an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 25 publications
4
21
2
7
Order By: Relevance
“…A pink discoloration of the albumen may develop due to the diffusion of iron, stored in the yolk, to the albumen where it binds ovotransferin . A recent study showed that dietary CLA increased the level of C18:0 in the vitelline membrane (Watkins et al, 2003). The CLA isomer primarily involved in these adverse effects is thought to be the t-10, c-12 CLA isomer.…”
Section: Discussionmentioning
confidence: 99%
“…A pink discoloration of the albumen may develop due to the diffusion of iron, stored in the yolk, to the albumen where it binds ovotransferin . A recent study showed that dietary CLA increased the level of C18:0 in the vitelline membrane (Watkins et al, 2003). The CLA isomer primarily involved in these adverse effects is thought to be the t-10, c-12 CLA isomer.…”
Section: Discussionmentioning
confidence: 99%
“…em acúmulo de ácidos graxos saturados, os quais conduzem a uma mudança da composição dos ácidos graxos nos tecidos dos animais (Watkins et al, 2003).…”
Section: Means Followed By Different Letters Within a Row Differ (P>0unclassified
“…A utilização de CLA tem sido objeto de pesquisas sobre ácidos graxos, em virtude de seus benefícios à saúde humana (Whigham et al, 2000). O fornecimento de CLA em dietas para suínos, aves e peixes tem melhorado suas características de produção (Park et al, 1997;Ostrowska et al, 1999;Twibell et al, 2000;Yang et al, 2002).…”
Section: Introductionunclassified
“…When a control fat or oil is unknown, the fatty acid composition (including the degree of unsaturation) and the varying chain lengths are useful for establishing the distinction between liquid oils and solid fats; the classification into drying, semi-drying, and nondrying oils; and the discrimination of types of fats and oils. Fatty acid composition is frequently analyzed by gas chromatography (GC) [4][5][6][7][8][9][10] and gas chromatography-mass spectrometry (GC-MS) [1][2][3][11][12][13][14] of saponifiables 1,2,4,5,11-13 for their classification, or for the discrimination of fats and oils. When fats and oils are saponified, saponifiables are obtained in the form of fatty acid salts, such as potassium salts in an aqueous layer.…”
Section: Introductionmentioning
confidence: 99%